Maxillary Osteomyelitis: A Rare Entity - Ayaaz Habib; Nagaraj Sivaji; Tauseef Ashraf (Case Reports in Otolaryngology)
Osteomyelitis of the maxilla is now a rare event with the advent of antibiotics. The two predominant causes are odontogenic infections and sinusitis. Immunocompromised states such as diabetes, HIV, and malnutrition increase the risk of osteomyelitis. It is important to recognize this early as it is a difficult entity to treat with potentially serious consequences. We report an unusual case of right sided maxillary osteomyelitis in a lady with poorly controlled diabetes in rural Lincolnshire. Biopsy of the right maxillary bone showed features of acute osteomyelitis. This responded well to a prolonged course of oral antibiotics.